WRITING PRACTICES OF EDUCATORS AS A FORMATIVE EXPERIENCE IN THE SCHOOL - Pinto, Keila Santos [UNESP]; Chaluh, Laura Noemi [UNESP] (Univ Metodista Piracicaba-unimep, 2017)
This paper presents part of a master's research that sought to understand the performance of the coordinator teacher, in the context of formation in the school, through the writing practices performed by the teachers and the coordinator teacher in a public preschool, located at Sao Paulo state. The investigative path of the research was based on the narrative of lived experiences (LIMA, GERALDI and GERALDI, 2015), and the data was analyzed from Ginzburg's indiciary paradigm (1989). As a coordinator teacher, researching your own practice, the intention was to mobilize a formative experience, which enhanced the interlocution between educators, an exercise that triggered reflection on the potentialities and limitations of the existing formative practices in the school, by legitimizing the school as space-time of knowledge and meaning production. One of the proposals of this interlocution was the HTPC (Collective Pedagogical Work Hours) diary, a collective action of writing that made possible to propose different forms of organization of this formation space, when promoting the movement of the words, the freedom to speak about yourself and about the other, the strengthening of the intimacy and trust relationships and the sharing of feelings and knowledge.
Keywords: Coordinator Teacher; Continued Education; School; Narratives